Parenchymal hematoma and total lesion volume in combined IV/IA revascularization stroke therapy. (10th August 2011) - Tao, Haiyang; Ramadas, Gowri; Carrozzella, Janice; Khatri, Pooja; Broderick, Joseph; Spilker, Judith; Tomsick, Thomas; ,
Abstract : Background and purpose: A positive correlation between large parenchymal hematoma (PH) volume and large CT lesion volume in subjects treated with intravenous (IV) recombinant tissue plasminogen activator (rtPA) as well as placebo controls was identified in the European Cooperative Acute Stroke Study II (ECASS II). A study was undertaken to examine the relationship between PH volume and total lesion volume (including both cerebral infarction and hemorrhage) in subjects with symptomatic parenchymal hematoma (sPH) treated with combined IV and intra-arterial (IA) rtPA in the Interventional Management of Stroke (IMS) studies. Methods: Hematoma and lesion volumes were measured planimetrically and by the ABC/2 method in 105 subjects from IMS studies I and II following combined IV and IA rtPA treatment. PH type 1 or 2 was determined by dichotomizing at >30% of lesion volume. Hematoma and lesion volumes for both symptomatic PH1 (sPH1) and PH2 (sPH2) types were compared using both measurement methods. Both sPH types were compared for baseline NIH Stroke Score, baseline Alberta Stroke Program Early CT score and treatment revascularization score based on the planimetric volume method. Results: The volume of sPH1 and sPH2 did not differ by either method of measurement. Subjects with sPH2 had a lower lesion volume compared with all PH1 (p=0.004) and sPH1 (p=0.02) by both methods. The ABC/2 method overestimated PH volume by 55±33% and lesion volume by 34±22% for sPH compared with the planimetric method. Conclusions: In IMS I and II, hemorrhages in subjects with sPH2 were similar in volume to those in subjects with sPH1 and were associated with a smaller rather than a larger total lesion volume compared with other PH in the setting of combined IV/IA therapy. The use of PH2 as a sole surrogate for sPH in studies of stroke treatment may underestimate the incidence of clinically significant hemorrhage.